1997
DOI: 10.5271/sjweh.201
|View full text |Cite
|
Sign up to set email alerts
|

Specific antibodies against methyltetrahydrophthalic anhydride and risk factors for sensitization in occupationally exposed subjects

Abstract: The following articles refer to this text: 2001;27(2): 133-139; 2003;29(4):297-303

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…10 Similar high frequencies of specific IgE antibody detection have been reported for tetrachlorophthalic anhydride (TCPA) and methyltetrahydrophthalic anhydride (MTHPA), with each of seven cases of TCPA-induced occupational asthma displaying specific IgE antibody 11 and 63% of MTHPAexposed workers testing positive for specific IgE and a significant correlation between work-related ocular or nasal symptoms and the detection of MTHPA-specific IgE antibody. 12 For other acid anhydrides, such as phthalic anhydride (PA) and maleic anhydride (MA), the evidence for IgE-mediated disease is less compelling. Published reports of patients with measurable anti-MA IgE antibody are sparse, with one patient reported with low levels of specific IgE antibodyinvestigations, however, a further seven individuals with respiratory symptoms and occupational exposure to MA and other acid anhydrides failed to display detectable anti-MA IgE antibody.…”
Section: Introductionmentioning
confidence: 99%
“…10 Similar high frequencies of specific IgE antibody detection have been reported for tetrachlorophthalic anhydride (TCPA) and methyltetrahydrophthalic anhydride (MTHPA), with each of seven cases of TCPA-induced occupational asthma displaying specific IgE antibody 11 and 63% of MTHPAexposed workers testing positive for specific IgE and a significant correlation between work-related ocular or nasal symptoms and the detection of MTHPA-specific IgE antibody. 12 For other acid anhydrides, such as phthalic anhydride (PA) and maleic anhydride (MA), the evidence for IgE-mediated disease is less compelling. Published reports of patients with measurable anti-MA IgE antibody are sparse, with one patient reported with low levels of specific IgE antibodyinvestigations, however, a further seven individuals with respiratory symptoms and occupational exposure to MA and other acid anhydrides failed to display detectable anti-MA IgE antibody.…”
Section: Introductionmentioning
confidence: 99%
“…Welinder et al 12) stated that 5 of 7 workers positive for HHPA-specific IgE in the group with lowest exposures reported frequent shorttime (minutes per day) exposures exceeding 50 µg/m 3 . In our previous study of a condenser plant using MTHPA 17) , no significant differences were found in the frequency of positive specific IgE or work-related symptoms between workers continuously and intermittently exposed. These findings indicate that short-time peak exposures may have a great impact on the development of specific IgE or workrelated symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In occupational environments a history indicating an immediate-type of allergy without demonstrable specific IgE has been observed among bakers (Kraut et al 1992). In studies of allergy caused by phthalic anhydrides, an association has been suspected between IgG 4 antibodies and hypersensitivity symptoms (Nielsen et al 1988;Nordman et al 1987) or phtalic anhydride allergy (Pakarinen et al 2002), but also studies on the same topic have been published that have not shown any association (Yokota et al 1997). …”
Section: Introductionmentioning
confidence: 96%